2022
DOI: 10.4103/njms.njms_34_20
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric norms for the north Indian population

Abstract: The cephalometric norms for orthognathic surgery (COGS analysis) are the standard benchmark in cephalometrics for any orthognathic surgical diagnosis and treatment planning. Since the introduction of cephalometrics by Broadbent, numerous studies have been conducted to establish craniofacial norms of different ethnicities. Most of these studies, however, determined craniofacial norms for Caucasian people and may not be applicable to other ethnic groups due to differences in their facial appearance. Therefore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…But we still use Caucasian norms for diagnosis and treatment planning of orthognathic surgery for North Indians. Therefore, it is essential to have definitive norms for each ethnic population 18 . According to Balakrishnan et al, most of the studies for prediction of difficult airway intubation have been based on measurements in Caucasians, and the cut‐off values set by them cannot be extrapolated to the Indian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But we still use Caucasian norms for diagnosis and treatment planning of orthognathic surgery for North Indians. Therefore, it is essential to have definitive norms for each ethnic population 18 . According to Balakrishnan et al, most of the studies for prediction of difficult airway intubation have been based on measurements in Caucasians, and the cut‐off values set by them cannot be extrapolated to the Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to have definitive norms for each ethnic population. 18 According to Balakrishnan et al, most of the studies for prediction of difficult airway intubation have been based on measurements in Caucasians, and the cut-off values set by them cannot be extrapolated to the Indian population. Accordingly, they have established that the upper limit for the normal ratio of height to thyromental distance to predict difficult intubation in the South Indian population is 17.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the inhabitants of Northern India, differences were also found in the COGS analysis indicators compared to European data, namely, they have lower values of the base of the skull, height of the face, higher values of the chin protrusion and the inclination of the mandibular incisors [10]. A similar kind of study, however, regarding residents of East India revealed the following features compared to European data: higher values of protrusion of the upper and lower lips, prognathia of the lower jaw [21].…”
Section: Table 1 the Value Of Cogs Teleroentgenometric Indicators Rel...mentioning
confidence: 90%
“…A systematic review of cephalometric norms for the north Indian population that contrasted it with Caucasians was published by [16]. He noted that the north Indian people had prognathic maxilla and mandible, more protruding chin, more inclined mandibular incisors, decreased middle third face height, as well as lower ramal and corpus length [16].…”
Section: Introduction and Review Of The Literaturementioning
confidence: 99%